2020
DOI: 10.3390/s20216118
|View full text |Cite
|
Sign up to set email alerts
|

A Portable System for Remote Rehabilitation Following a Total Knee Replacement: A Pilot Randomized Controlled Clinical Study

Abstract: Rehabilitation has been shown to improve functional outcomes following total knee replacement (TKR). However, its delivery and associated costs are highly variable. The authors have developed and previously validated the accuracy of a remote (wearable) rehabilitation monitoring platform (interACTION). The present study’s objective was to assess the feasibility of utilizing interACTION for the remote management of rehabilitation after TKR and to determine a preliminary estimate of the effects of the interACTION… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 55 publications
(67 reference statements)
2
21
0
Order By: Relevance
“…Doiron-Cadrin et al [ 63 ] found high satisfaction and clinically meaningful within-group improvements in pain and function with a 12-week prehabilitation program using real-time videoconferencing, which were similar to those in people who received the 12-week prehabilitation program in person. Similar outcomes between digital and in-person PT interventions have also been reported in individuals after KR for video-based and inertial motion sensor–based digital health interventions [ 63 - 66 ]. However, some outcomes (physical activity, muscle strength, exercise behavior, climbing stairs, walking, and body pain) favored in-person PT at longer follow-up periods (2, 4, 12, or 18 months after the intervention) [ 65 , 52 ].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Doiron-Cadrin et al [ 63 ] found high satisfaction and clinically meaningful within-group improvements in pain and function with a 12-week prehabilitation program using real-time videoconferencing, which were similar to those in people who received the 12-week prehabilitation program in person. Similar outcomes between digital and in-person PT interventions have also been reported in individuals after KR for video-based and inertial motion sensor–based digital health interventions [ 63 - 66 ]. However, some outcomes (physical activity, muscle strength, exercise behavior, climbing stairs, walking, and body pain) favored in-person PT at longer follow-up periods (2, 4, 12, or 18 months after the intervention) [ 65 , 52 ].…”
Section: Resultssupporting
confidence: 59%
“…In people with KOA, the benefits of digital health for exercise and physical activity interventions in people with KOA appear mixed. In contrast, in people with KR, many studies reported significant improvements in self-reported outcomes with digital exercise interventions that were similar to in-person treatments [ 63 - 66 ]. Although the different technologies used in these studies (eg, websites, telephone, mobile apps, videoconferencing, and multi-technology systems) were generally acceptable to people with KOA and KR, some participants who used telephone-based interventions stated the need for visual contact with their physical therapists [ 96 - 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…For chronic musculoskeletal spinal conditions, results were unambiguous and warrant further investigations [ 25 ]. Most studies in the field of orthopaedics investigated the efficacy of telemedicine in postoperative care [ 27 32 ]. In the field of trauma, the success of prevention programs was evaluated in two studies [ 33 , 34 ], pre-treatment optimisation in one study [ 35 ], and conservative treatment/outpatient care in four studies [ 36 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a potential role for IMUs to be used to supplement existing post-operative function measures (i.e., PROMs and PBOMs) and provide additional diagnostic value through clinic- and home-based RPM [ 7 ]. IMUs have been applied extensively in younger orthopaedic patients following sports injury [ 17 , 18 , 19 , 20 ] and are becoming increasingly common in evaluation of knee arthroplasty procedures [ 7 , 21 , 22 , 23 , 24 ]. However, many of these previous studies reported functional performance based on a single stand-alone function score, as opposed to using a variety of gait parameters, or have not combined IMU measurements with existing validated PROMS and PBOMs.…”
Section: Introductionmentioning
confidence: 99%